(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
Guided Bone Regeneration (GBR) is a standard surgical procedure to augment jawbone volume, conventionally using titanium meshes or collagen membranes - each with inherent limitations such as stress shielding, imaging artifacts, or insufficient mechanical stability. Here, we introduce a novel 3D-printed, patient-specific biodegradable mesh fabricated via Arburg plastic freeforming (APF) using PLDLLA/?-TCP composite. Three design variants were fabricated: A solid configuration for maximal strength, a porous structure (50% infill) to minimize fibrous tissue ingrowth, and a gyroid design to promote angiogenesis. Our results demonstrate high dimensional accuracy (<1% deviation) and pore sizes of 243±17 µm (porous) and 620±64 µm (gyroid). Mechanical testing revealed that the solid design achieved a biaxial flexural strength of 129±13 MPa, significantly outperforming the porous (26±5 MPa) and gyroid designs (23±2 MPa). These results lay the foundation for further optimization, including hybrid designs that integrate robust mechanical support with favorable biological properties, ultimately eliminating the need for secondary surgery.